(3eG CHQRJg GdCbOGQ aj fUQI Phj GdefGbH hGdCSQGQs - (3CHh GdMSf Ydj Hf XGgQ GdhJQj GdMSfj GdeOfj GdMfaj,J (B1322 (3g` s
(3ChdgG (B:s
(3hHYO , adeG ef Gddg Ydi HGdQMdI Edi GdOjGQ GdeZQHjI hGLJeYJ HYdeGFgG cKjQkG eG cfJ CSeYge jPcQhf JCdjakG aj GdOjGQ GdZdhjI s
(3BNQgG (B:s
(3hfSCdc HMQeI MHjHc Cf JhabfG HeG jQVjc YfG hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B13 - (3U(B31s
(3QO ajg Ydi eDda cJGH GdLjT GdYQeQes
(3dCHj YHOGddg eMeO CcShS GdeQGcTj MjK fbV aj cJGH GdePgH GdhgGHjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3Odjd eDQN GdeZQH GdCbUi (B- (3U (B522 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B363 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B1115) s
Keywords: (3GdJGQjNs